(3MGTjI Gdcahj Ydi TQM MSjfjI GdCfWGcjs - (3Gdcahj, eMeO Hf MejO Hf eUWai, (B1174 (3g`s ((3jhSa Hf EHQGgje GdHGfjhfjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj COHfG HBOGH GdefGXQI JCOjHG (B...(3deG cGfJ GdQSGdI GdMSjfjI eY TQMgG CMSf eG UfaJ aj afgG CPgi eY UaQ MLegG hbdI fLegG dG jZGOQ UZjQI hdG cHjQI EdG (B...s
(3BNQgG (B:s
... (3dFdG jTJZd Pgfg HLdGdI bOQ GdNUe hGdGNJTGe Cj hHGdGNJTGe ajSbW MOI Pgfg hObJg acQg hjahJ GdeQGe Yf GdcdGe Cf dG jMJSH hGdMb Cf ef CNdU ZQVg dG jHGdjg (B... (3JeJs
(3JHUQI GdYfhGf (B:s
(3jHOh Cf TGQM GdMSjfjI gh eMeO HjQ GdHQchj ceG CdeM GdHZOGOj aj gOjI GdYGQajfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\270s
(3gOjI GdYGQajf (B2\332s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs